2014
DOI: 10.1039/c4ra06055e
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed oxidative C–H arylation of heterocycle embedded thiophene/furan with aryl boronic acid/ester

Abstract: Palladium catalyzed oxidative C-H arylation of heterocycle embedded thiophenes with aryl boronic acids is described. This method is found to display high C5-selectivity and thus enabled rapid access to 2,5disubstituted thiophenes. Furan analogs also exhibited a similar selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…For example, Wu and co‐workers demonstrated a low catalyst loading direct arylation of 2‐(thiophen‐2‐yl)pyridine which resulted in C5‐arylated product excluding the pyridine ring acting as a directing group . A similar behavior was observed by Nagarajan et al in arylation of N‐heterocycle embedded thiophenes and furans with aryl boronic acids under Pd‐catalyzed oxidative reaction conditions which resulted in high C(5)–H arylation selectivity thus enabling an easy access to 2,5‐disubstituted thiophenes …”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…For example, Wu and co‐workers demonstrated a low catalyst loading direct arylation of 2‐(thiophen‐2‐yl)pyridine which resulted in C5‐arylated product excluding the pyridine ring acting as a directing group . A similar behavior was observed by Nagarajan et al in arylation of N‐heterocycle embedded thiophenes and furans with aryl boronic acids under Pd‐catalyzed oxidative reaction conditions which resulted in high C(5)–H arylation selectivity thus enabling an easy access to 2,5‐disubstituted thiophenes …”
Section: Introductionsupporting
confidence: 53%
“…[8] A similar behavior was observed by Nagarajan et al in arylation of Nheterocycle embedded thiophenes and furans with aryl boronic acids under Pd-catalyzed oxidative reaction conditions which resulted in high C(5)-H arylation selectivity thus enabling an easy access to 2,5-disubstituted thiophenes. [9] One of the first examples of exclusive palladium-catalyzed C3-arylation of thiophenes was reported by Miura and co-workers by using a 3-carbamoyl moiety as the directing group. [10] Furthermore, Doucet et al observed that palladium-catalyzed direct arylation of furans and thiophenes containing a secondary carbamoyl group at the C2-position proceeded regioselectively either at C3-or C5-position strongly depending on the reaction conditions used.…”
Section: Introductionmentioning
confidence: 99%
“…α-Arylfurans, which have potentially useful bioactivities and physical properties, are usually prepared by means of Suzuki coupling of 2-furanylboronic acid with aryl halides or by direct arylation of α-furyl C–H bonds with aryl halides. α-Arylfurans can also be prepared by the oxidative coupling of aryl boronic acids with α-furyl C–H bonds in the presence of a strong oxidant such as Mn­(OAc) 3 , Ag 2 CO 3 , or TEMPO. However, oxidative coupling mediated by O 2 , which is an environmentally benign oxidant, has never been reported.…”
Section: Resultsmentioning
confidence: 99%
“…[96] Moreover, indoles, pyrroles, furans and thiophenes could be arylated in a chemo-and site-selective fashion. [97] Proposed mechanisms include precoordination of the palladium to the heteroatom, as well as an electrophilic mechanism involving ArPd(+II) species. The selectivity of the C-H arylations strongly depends on the electronic properties of the electrophiles and substrates, on the nature of the palladium catalyst, as well as the additives in the reaction.…”
mentioning
confidence: 99%